Computerized Spatial Navigation Training During 14 Days of Bed Rest in Healthy Older Adult Men: Effect on Gait Performance. - Marusic, Uros; Kavcic, Voyko; Giordani, Bruno; Gerževič, Mitja; Meeusen, Romain; Pišot, Rado (Psychology & Aging, 2015)
Prolonged physical inactivity or bed rest (BR) due to illness or other factors can result in significant declines in physical health and even cognitive functions. Based on random selection, 7 healthy older adult men received computerized spatial navigation training, while 8 served as active controls during 14-day BR. Greater post-BR declines were seen in normal and complex (dual-task) walking for the control as compared to intervention group, suggesting that computerized spatial navigation training can successfully moderate detrimental BR effects. Findings underline the generalization of cognitive-based intervention to the motor domain and potentially support their use to supplement BR interventions (e.g., exercise and nutrition).